2021
DOI: 10.1039/d1cs00846c
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoglycolysis: catabolic pathways for metabolism of sulfoquinovose

Abstract: A biochemical, structural and mechanistic perspective on the pathways of sulfoglycolysis for catabolism of the sulfosugar sulfoquinovose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 89 publications
(152 reference statements)
0
22
0
Order By: Relevance
“…Previously, there has been no evidence that SQDG can be completely metabolized by sulfoglycolytic organisms. Instead, various non-specific lipases have been reported that can cleave the lipid chains ( Snow et al., 2021 ), suggesting that the sulfo-SMO pathway is used in partnership with non-sulfoglycolytic organisms (possibly including plants) that excise and metabolize the energy-rich lipid chains of SQDG, releasing the sulfosugar SQGro. However, the ability of SmoF to bind SQDG suggests that A. tumefaciens can on its own achieve the import of SQDG and SQMG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, there has been no evidence that SQDG can be completely metabolized by sulfoglycolytic organisms. Instead, various non-specific lipases have been reported that can cleave the lipid chains ( Snow et al., 2021 ), suggesting that the sulfo-SMO pathway is used in partnership with non-sulfoglycolytic organisms (possibly including plants) that excise and metabolize the energy-rich lipid chains of SQDG, releasing the sulfosugar SQGro. However, the ability of SmoF to bind SQDG suggests that A. tumefaciens can on its own achieve the import of SQDG and SQMG.…”
Section: Discussionmentioning
confidence: 99%
“…SQDG is a major global reservoir of organosulfur with an estimated 10 ​Pg produced annually ( Goddard-Borger and Williams, 2017 ; Harwood and Nicholls, 1979 ). The catabolism of SQDG occurs in a wide range of gram-positive and gram-negative bacteria through one of five sulfoglycolytic pathways ( Snow et al., 2021 , J. Liu et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…26 S -SLA is a metabolic product of the breakdown of sulfoquinovose through the pathways of sulfoglycolysis. 48 It was proposed that S -SLA could undergo direct reductive amination to R -AHPS but would require stereochemical inversion catalysed by a racemase. Alternatively, S -SLA could be inverted to R -SLA prior to reductive amination.…”
Section: R-3-amino-2-hydroxypropanesulfonatementioning
confidence: 99%
“…The annual global production of SQ is estimated at 10 10 tons per annum (Harwood and Nicholls 1979 ), and thus, the degradation of this sulfosugar is an important arm of the global biogeochemical cycle. The degradation of sulfoquinovose occurs through pathways of sulfoglycolysis and provides access to its constituent carbon and generates ATP and reducing equivalents (NADH/NADPH) (Benson and Shibuya 1961 ; Snow et al 2021 ). The sulfoglycolytic Embden–Meyerhof–Parnas (sulfo-EMP) (Denger et al 2014 ; Sharma et al 2021 ), Entner–Doudoroff (sulfo-ED) (Felux et al 2015 ), and sulfofructose transaldolase (sulfo-SFT) (Frommeyer et al 2020 ; Liu et al 2020 ) pathways cleave the 6-carbon chain of SQ into two 3-carbon fragments, one of which is utilized in primary metabolism, while the other containing the sulfonate group is converted to either sulfolactate (SL) or 2,3-dihydroxypropanesulfonate (DHPS) and excreted.…”
Section: Introductionmentioning
confidence: 99%